The Effect of Differences In Soil Nailing Length On The Value Of Safety Factor (Case Study: D.I. Batang Sinamar Project) - Fitria Wahyuni; Ragil Purnamasari; Jannatul Firdausi Nuzula (Journal of Civil Engineering Science and Technology (CI-TECH), 2022)
Construction of irrigation canals in the Batang Sinamar area, Sumatra, is carried out in the highlands. The soil on the slope is known to have soft soil consistency. So, it is necessary to analyze the reinforcement design for slopes with soft soil conditions to avoid problems in the future. In this plan, design analysis is carried out using soil nailing, which is planned with different depths, namely 8 meters and 10 meters. Reinforcement analysis will be carried out with the FEM program. From the analysis results, a comparison of the effectiveness of the design will be carried out in terms of cost analysis and the method of implementation. From the analysis results, it was found that the length of soil nailing of 8 meters was more effective in terms of the safety factor value, cost analysis, and duration of the implementation method.